Szanse osób niepełnosprawnych na znalezienie pracy - Jabłońska, Angelika (The Disabled Persons Chances to Find an Employment, 2005)
The number of the disabled persons is continuously increasing as a consequence of a life style, the civilization diseases and longer average life span. It is not so easy to define a disability. There are different definitions and classifications on the disabled persons. The World Health Organization distinguishes different disability grades, such as: impairment, disability and handicap. You can also classify the disabled persons as: disabled only biologically, disabled only legally and disabled both biologically and legally. The disabled persons assistance programs aim at disabled persons joining or returning to the active life. Unfortunately, taking into account demographic, social and economic reasons, it is extremely hard to attain objectives of the programs. A particulary unfavourable situation of the disabled persons on a labour market comes from a high unemployment rate in Polish labour market and a conviction that the disabled persons are worse employees alike. The disabled persons, due to the limitations they have, can apply for a post in the disabled persons labour market and in an open labour market as well. In the open labour market there is a competition between healthy persons and disabled ones. Apart from that there are the ob.stacles in the disabled persons employment inherent in the disabled people, a labour environment and the employers alike. A hypothesis that there will be an increase in work places for the disabled persons as well as their professional and social rehabilitation chances as the service sector is developing seems to be the right one. Agriculture and industry, since require physical strength and the work is often done in harmful conditions, do not give such chances. Mental and psychical limitation in connection with physical ones minimaze chances to find a job. It is therefore important to launch the diverse means for the disabled persons to find a job and to motivate employers to employ them.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1089, s. 92-102